Test Anxiety in Adolescent Students: Different Responses According to the Components of Anxiety as a Function of Sociodemographic and Academic Variables - Torrano, Rosa; Ortigosa, Juan M.; Riquelme, Antonio; Méndez, Francisco J.; López-Pina, José A. (Frontiers in Psychology, 2020)
Objective: Test anxiety is a construct that has scarcely been studied based on Lang's three-dimensional model of anxiety. The objective of this article is to investigate the repercussion of sociodemographic and academic variables on different responses for each component of anxiety and for the type of test in adolescent students. Method: a total of 1,181 students from 12 to 18 years old (M = 14.7 and SD = 1.8) participated, of whom 569 were boys (48.2%) and 612 girls (51.8%). A sociodemographic questionnaire and the Cuestionario de Ansiedad ante los examenes-Adaptado (CAEX-A) [Test Anxiety Questionnaire-Adapted] an adaptation for Spanish secondary school levels (ESO) and Baccalaureate were administered. Results: Girls scored higher on the cognitive and physiological components of test anxiety than boys, the intensity of the physiological response increasing with age. Baccalaureate level students reported more physiological anxiety than those of ESO level. Students with better grades in the previous year presented more physiological anxiety, while the cognitive and avoidance components were more present in those with lower grades. Participants reported that the three types of tests that cause them the most anxiety were oral tests in front of the class, mathematics tests, and essay tests. Conclusion: The relevance is highlighted of the physiological component of test anxiety in adolescents and the implication of the variables studied. These results serve to design specific intervention programs to manage anxiety in situations of academic assessment.